Hypoxia-driven immunosuppression contributes to the pre-metastatic niche - Jaclyn Sceneay; Belinda S. Parker; Mark J. Smyth; Andreas Möller (2012)
Primary tumor cells create favorable microenvironments in secondary organs, termed pre-metastatic niches, that promote the formation of metastases. Using immune competent syngenic breast cancer mouse models, we have recently demonstrated that factors secreted by hypoxic tumor cells condition pre-metastatic niches by recruiting CD11b+/Ly6Cmed/Ly6G+ myeloid cells and suppressing natural killer cell functions.